2020
DOI: 10.1002/pbc.28281
|View full text |Cite
|
Sign up to set email alerts
|

Fathers' psychological responses to pediatric cancer–induced financial distress

Abstract: Background:To describe how pediatric cancer-induced financial distress and perceptions of their social role affected fathers' psychological responses to this distress, and quality of life (QOL) for them and their families. Procedure:We analyzed father-only responses from a larger cross-sectional survey study about the impact of pediatric cancer-induced financial distress on parents. Our analytic sample was n = 87 fathers who participated in the larger study. We analyzed their data using descriptive statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In addition, fathers were described as having less access to emotional support, from both personal support and welfare systems. Previous research has found that fathers' sense of pressure to take the breadwinning role when a child is treated for cancer may cause both financial trauma and consequential psychological distress (Santacroce et al, 2020). Our study suggests that despite the progress of gender equality in many aspects of society the past decades, mothers and fathers are still met with different expectations when it comes to parenting a seriously ill child, even in a country such as Sweden, where gender equality has been extensively advocated.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, fathers were described as having less access to emotional support, from both personal support and welfare systems. Previous research has found that fathers' sense of pressure to take the breadwinning role when a child is treated for cancer may cause both financial trauma and consequential psychological distress (Santacroce et al, 2020). Our study suggests that despite the progress of gender equality in many aspects of society the past decades, mothers and fathers are still met with different expectations when it comes to parenting a seriously ill child, even in a country such as Sweden, where gender equality has been extensively advocated.…”
Section: Discussionmentioning
confidence: 67%
“…First, when a child is diagnosed with cancer, parents plan a daily routine that prioritizes coping with the child’s disease. While determining the treatment method, parents play multiple roles, such as providing emotional support and financial support to their child as a patient’s guardian [ 5 ]. As the patient begins to receive cancer treatment in earnest, parents face new events such as repeated diagnostic tests, drug injections, invasive procedures, and physical changes in their child.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the project might help reducing expenses for families due to fewer travels and less personal days taken from work for both parents, but also missed daycare or school days for healthy siblings. Financial disruption could have a substantial influence on parental distress during and after treatment of childhood cancer and must be carefully considered [25,26].…”
Section: Discussionmentioning
confidence: 99%